HIPS composite material and preparation method and application thereof

By using specific compounded antistatic agents and heat-resistant compatibilizers, the problem of poor compatibility between HIPS resin and antistatic agents was solved, and HIPS composite materials with excellent antistatic and heat-resistant properties were prepared, which are suitable for the electronic and electrical fields.

CN119613911BActive Publication Date: 2025-12-05KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411556155.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-12-05
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

HIPS resin has poor compatibility with antistatic agents, resulting in poor dispersion of antistatic agents, poor antistatic effect of the product, and lack of heat resistance.

Method used

HIPS composite materials were prepared by melt extrusion using a specific combination of antistatic agents and heat-resistant compatibilizers, such as sodium alkyl sulfonate and alkoxypropyl dihydroxyethylamine, as well as polyphenylene ether resin and GPPS resin, to improve compatibility and heat resistance.

Benefits of technology

The HIPS composite material exhibits low surface resistance and excellent antistatic properties at low addition levels, along with good durability and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005116490700000051
    Figure BDA0005116490700000051
  • Figure BDA0005116490700000062
    Figure BDA0005116490700000062
Patent Text Reader

Abstract

The application discloses a HIPS composite material and a preparation method and application thereof. The HIPS composite material comprises the following components in parts by weight: 49-70 parts of HIPS resin, 18-25 parts of composite antistatic agent, 10-20 parts of heat-resistant compatilizer, 2-6 parts of compatilizer and 3-5 parts of toughening agent. The composite antistatic agent comprises sodium alkyl sulfonate containing 8-14 carbon atoms and alkoxypropyl dihydroxyethyl amine. The heat-resistant compatilizer is selected from polyphenylene ether resin and / or GPPS resin. The melt flow rate of the polyphenylene ether resin is 25-45 g / 10 min under the test condition of temperature 315 DEG C and load 10 kg. The number average molecular weight of the GPPS resin is 4.0*10 4 8.5*10 4 g / mol. The HIPS composite material has not only good antistatic property but also excellent heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of modified plastics, and more particularly relates to a HIPS composite material and a preparation method and application thereof. BACKGROUND

[0002] Antistatic polymer belongs to a kind of functional materials, which can inhibit the generation and accumulation of electric charge to a certain extent. Antistatic materials are most widely used in the electronic and electrical industry. In the production process of electronic products, static electricity may cause problems such as component damage and data loss. Antistatic materials can effectively reduce the influence of static electricity and improve the reliability and stability of products. The main application scenarios include antistatic packaging, antistatic coating and antistatic floor, etc.

[0003] Polystyrene material has the advantages of easy molding, good rigidity, easy dyeing, etc. However, polystyrene is brittle and has low impact strength. Therefore, HIPS resin (high impact polystyrene) gradually replaces polystyrene in some fields. HIPS resin is a kind of thermoplastic material modified by elastomer from polystyrene, which is a two-phase system composed of rubber phase and continuous polystyrene phase. It has the dimensional stability of general polystyrene and better impact strength and rigidity. It has developed into an important polymer commodity in the world, making it have a wide range of applications.

[0004] However, due to the poor polarity of HIPS resin, when adding antistatic agents with high polarity for modification, the compatibility between HIPS resin and antistatic agents is often poor, which leads to poor dispersion of antistatic agents in the product, and ultimately poor antistatic effect of the product.

[0005] Therefore, how to solve the dispersion problem of antistatic agents in HIPS resin and improve the antistatic performance of the product has become an important problem to be solved. SUMMARY

[0006] In view of the above technical problems, the primary purpose of the present application is to provide a HIPS composite material which not only has good antistatic performance, but also has excellent heat resistance.

[0007] The second purpose of the present application is to provide a preparation method of the HIPS composite material.

[0008] The third purpose of the present application is to provide an application of the HIPS composite material in the field of electronics and electrical appliances.

[0009] In order to achieve the above purposes, the present application is realized by the following technical solutions:

[0010] The application claims a HIPS composite material, comprising the following components in parts by weight: 49-70 parts of HIPS resin, 18-25 parts of composite antistatic agent, 10-20 parts of heat-resistant compatibilizer, 2-6 parts of compatibilizer, and 3-5 parts of toughening agent; wherein the composite antistatic agent comprises a first antistatic agent and a second antistatic agent; the first antistatic agent is sodium alkyl sulfonate containing 8-14 carbon atoms, and the second antistatic agent is alkoxypropyl dihydroxyethylamine; and the heat-resistant compatibilizer is selected from polyphenylene ether resin and / or GPPS resin.

[0011] The application uses the first antistatic agent and the second antistatic agent for compounding, which has excellent synergistic effect of improving the antistatic performance. The two are used simultaneously, and due to the interaction, they cannot all migrate to the surface of the polymer and be lost, but can effectively transfer the surface charge, so that the HIPS composite material has good antistatic performance and good durability.

[0012] Further, the inventors have found through research that using polyphenylene ether resin with a melt flow rate in a specific range or GPPS resin with a number average molecular weight in a specific range as the heat-resistant compatibilizer can not only significantly improve the compatibility of the composite antistatic agent in the HIPS resin system, but also further improve the heat resistance of the HIPS resin system. The polyphenylene ether resin has good mutual solubility with the HIPS resin, which can promote better mutual solubility of the composite antistatic agent and the HIPS system, and reduce interface defects.

[0013] The application provides a HIPS composite material, which greatly improves the antistatic performance of the HIPS resin system by using specific compounded antistatic agents, specific heat-resistant compatibilizers, and other components in the system, realizes low surface resistance at a low addition amount, and has good durability. In addition, the obtained HIPS composite material also has excellent heat resistance.

[0014] Specifically, the mass percentage of the HIPS resin in the HIPS composite material is not less than 46.6%. Further preferably, the mass percentage of the HIPS resin in the HIPS composite material is not less than 53.7%.

[0015] Preferably, the mass ratio of the first antistatic agent to the second antistatic agent is 1:1-4. Further preferably, the mass ratio of the first antistatic agent to the second antistatic agent is 1:1.2-3. Most preferably, the mass ratio of the first antistatic agent to the second antistatic agent is 1:1.5.

[0016] Preferably, the melt flow rate of the polyphenylene ether resin under the test conditions of temperature 315℃, load 10kg is 25-45g / 10min. Further preferably, the melt flow rate of the polyphenylene ether resin is 26-43g / 10min. Specifically, the melt flow rate of the polyphenylene ether resin in the present application can be 25g / 10min, 30g / 10min, 35g / 10min, 40g / 10min, 45g / 10min, etc., or the interval range formed by any of the above values, such as 30-40g / 10min, 35-45g / 10min, etc., and the present application is not limited thereto. Specifically, the test standard of the melt flow rate of the polyphenylene ether resin is ISO1133-1-2011.

[0017] Preferably, the number average molecular weight of the GPPS resin is 4.0×10 4 -8.5×10 4 g / mol. Specifically, the number average molecular weight of the GPPS resin is 4.2×10 4 -6.2×10 4 g / mol. Specifically, the number average molecular weight of the GPPS resin in the present application can be 4.5×10 4 g / mol, 5.0×10 4 g / mol, 5.5×10 4 g / mol, 6.0×10 4 g / mol, 6.5×10 4 g / mol, 7.0×10 4 g / mol, 7.5×10 4 g / mol, 8.0×10 4 g / mol, etc., or the interval range formed by any of the above values, such as 4.2-7.0×10 4 g / mol, etc., and the present application is not limited thereto. The test method of the number average molecular weight of the GPPS resin is gel permeation chromatography using polystyrene standard measurement, and the solvent is tetrahydrofuran.

[0018] Preferably, the toughening agent is selected from one or more of styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene block copolymer (SEBS), styrene-acrylonitrile-acrylate rubber body (ASA), styrene-maleic anhydride copolymer (SMA), methyl methacrylate-butadiene-styrene terpolymer (MBS).

[0019] Preferably, in the toughening agent, the content of styrene is ≤60wt%. Further preferably, the content of styrene is ≤40wt%.

[0020] Specifically, the melt flow rate of the HIPS resin under the test condition of 200℃, load 5kg is 5-13g / 10min. Specifically, the test standard of the melt flow rate of the HIPS resin is ISO 1133-1-2011.

[0021] Preferably, the compatilizer is selected from one or more of polyethylene, polypropylene, chlorinated polyethylene, low density polyethylene, linear low density polyethylene. More specifically, the compatilizer is linear low density polyethylene.

[0022] Specifically, the first antistatic agent is sodium alkyl sulfonate containing 12-14 carbon atoms. Specifically, the surface resistance of the first antistatic agent is 6x10 7 Ω. Specifically, the surface resistance of the second antistatic agent is 3x10 7 Ω. The test method of the surface resistance is that a 2.0mm thick square plate is placed horizontally, and a surface resistance meter is placed tightly on it, and the surface resistance of the material is obtained by measuring the voltage and current value on the surface of the material.

[0023] Further, the present application claims a preparation method of the HIPS composite material, mixing HIPS resin, composite antistatic agent, heat-resistant compatilizer, compatilizer and toughening agent, melt extruding, granulating, to obtain the HIPS composite material.

[0024] Specifically, the screw rotation speed of the twin-screw extruder is 350-550rpm.

[0025] Specifically, the extrusion temperature is 240-260℃.

[0026] Further, the present application claims the application of the HIPS composite material in the field of electronic and electrical appliances. Specifically, the HIPS composite material is suitable for preparing printers, air conditioners and the like, especially for occasions with high requirements for antistatic performance and heat resistance.

[0027] Compared with the prior art, the present application has the following beneficial effects:

[0028] The present application provides a HIPS composite material, by using specific composite antistatic agent, specific heat-resistant compatilizer, and other components in the system, the antistatic performance of the HIPS resin system is greatly improved, the surface low resistance can be realized under low addition amount, and it has good durability. In addition, the HIPS composite material prepared also has excellent heat resistance. DETAILED DESCRIPTION

[0029] The present application is further explained by the following description and specific examples, which do not limit the application in any way. Unless otherwise defined, all reagents, methods and devices employed in the present application are those conventional in the art.

[0030] The raw materials of the examples and comparative examples are as follows:

[0031] HIPS resin 1, melt flow rate 5.2 g / 10 min (200 °C, 5 kg), PS 350K, China Taiwan Guojiao.

[0032] HIPS resin 2, melt flow rate 12.3 g / 10 min (200 °C, 5 kg), HI 425TVNL, South Korea Jinhu.

[0033] First antistatic agent 1, sodium tetradecyl sulfonate (CAS: 6994-45-2), Aldrich Reagent Company.

[0034] First antistatic agent 2, sodium dodecyl sulfonate (CAS: 2386-53-0), Aldrich Reagent Company.

[0035] Second antistatic agent, alkoxypropyl dihydroxyethyl amine (CAS: 71786-60-2), Aldrich Reagent Company.

[0036] Third antistatic agent, polyether amide, Pelestat-6500, Japan Sanyo Chemical Industries Co., Ltd.

[0037] Heat-resistant compatibilizer 1, polyphenyl ether resin, PPE LXN040, melt flow rate 26 g / 10 min (315 °C, 10 kg), Nantong Xingchen.

[0038] Heat-resistant compatibilizer 2, polyphenyl ether resin, PPE LXN035, melt flow rate 78 g / 10 min (315 °C, 10 kg), Nantong Xingchen Synthetic Material Co., Ltd.

[0039] Heat-resistant compatibilizer 3, polyphenyl ether resin, PPE PX100L, melt flow rate 43 g / 10 min (315 °C, 10 kg), Mitsubishi Corporation.

[0040] Heat-resistant compatibilizer 4, GPPS resin, number average molecular weight 4.2 x 10 4 g / mol (tested by gel permeation method with tetrahydrofuran as solvent), GP1441, Dow Chemical Company.

[0041] Heat-resistant compatibilizer 5, GPPS resin, number average molecular weight 6.2 x 10 4g / mol (tested by gel permeation method with tetrahydrofuran as solvent), GPPS-500NT, Sinopec.

[0042] Heat-resistant compatibilizer 6, GPPS resin, number average molecular weight of 1.2 x 10 5 g / mol (tested by gel permeation method with tetrahydrofuran as solvent), 818K, Tedia Chemical.

[0043] Toughening agent, SBS, YH-792E, Sinopec Baling Petrochemical Co., Ltd.

[0044] Compatibilizer: LLDPE, density of 0.92 g / cm 3 , DFDA-7042 (MAOMING), Maoming Petrochemical Co., Ltd.

[0045] Unless otherwise specified, each component used in each parallel example and comparative example is the same commercially available product.

[0046] Example 1

[0047] The weight parts of the raw materials used in Example 1 are shown in Table 1.

[0048] A preparation method of a HIPS composite material, the specific steps include:

[0049] The HIPS resin, the first and second antistatic agents, the heat-resistant compatibilizer, the compatibilizer and the toughening agent are mixed in a mixer at a rotating speed of 1200 rpm for 5 min; the obtained mixture is melt-extruded at 260℃ by a twin-screw extruder (length-diameter ratio of 40:1, rotating speed of 450 rpm), granulated and dried to obtain the HIPS composite material.

[0050] Examples 2-9

[0051] The weight parts of the raw materials used in each of the following examples are shown in Table 1.

[0052] The specific preparation steps of each of the following examples are the same as those of Example 1.

[0053] Comparative Examples 1-7

[0054] The weight parts of the raw materials used in each of the following comparative examples are shown in Table 2.

[0055] The specific preparation steps of each of the other comparative examples are the same as those of Example 1.

[0056] Table 1

[0057]

[0058]

[0059] Table 2 is the formulation components of each comparative example:

[0060] Table 2

[0061] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 HIPS Resin 1 65 65 65 65 80 65 65 First Antistatic Agent 1 20 / 8 / 8 8 8 Second Antistatic Agent / 20 / 12 12 12 12 Third Antistatic Agent / / 12 8 / / / Heat-Resistant Compatibilizer 1 15 15 15 15 0 / / Heat-Resistant Compatibilizer 2 / / / / / 15 / Heat-Resistant Compatibilizer 6 / / / / / / 15 Compatibilizer 3 3 3 3 3 3 3 Toughening Agent 2 2 2 2 2 2 2

[0062] The above examples and comparative examples are tested by using the following test standards.

[0063] Table 3

[0064] Test Item Unit Test Condition Test Standard Heat Distortion Temperature ℃ 1.8 MPa, side stand ASTM D648-2007 Surface Resistance Ω 2.0 mm square plate thickness ASTM D257-2007

[0065] The test method of surface resistance after boiling in water for 7 days: a 100*100*2mm square plate is injection molded by using an injection molding machine, the injection molding speed is medium, the injection molding pressure is 55MPa, the injection molding temperature is 250℃, and the cooling time is 10 seconds. The prepared square plate for testing is soaked in water medium at 60℃ for 7 days, then the square plate is taken out and dried in an 80℃ oven for 2 days, and then the surface resistance test is carried out.

[0066] Table 4 and Table 5 are the performance test results of each example and comparative example, respectively.

[0067] Table 4

[0068]

[0069]

[0070] Table 5

[0071] Test Item Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Surface Resistance (Ω) 3 x 10 9 ]] 6 x 10 10 ]]> 5 x 10 9 ]] 4 x 10 9 ]] 6 x 10 9 ]] 5 x 10 9 ]] 4 x 10 9 ]] Surface Resistance after boiling in water for 7 days (Ω) 7 x 10 10 ]] 3 x 10 11 ]] 4 x 10 10 ]] 3 x 10 11 ]] 6 x 10 10 ]]> 5 x 10 10 ]]> 4 x 10 10 ]] Heat Distortion Temperature (°C) 82 80 84 85 75 85 86

[0072] From the example data, it can be seen that the present application provides a HIPS composite material, by using specific complex antistatic agent, specific heat-resistant compatibilizer, and other components in the system, the antistatic performance of the HIPS resin system is greatly improved, and low surface resistance can be achieved at low addition amount. In the present application, the surface resistance of the HIPS composite material is ≤4*10 8 Ω, after boiling in water for 7 days, the HIPS composite material still has a low surface resistance, the surface resistance is ≤7*10 8 Ω, and the heat distortion temperature is ≥81℃.

[0073] From example 1, comparative example 1 to comparative example 4, it can be seen that the use of specific complex antistatic agent can better improve the surface resistance of the HIPS composite material, and still has a low surface resistance after boiling in water for 7 days, which reflects the stability of the antistatic performance of the HIPS composite material. It is difficult to achieve the technical effect by using only one of the antistatic agents or not using the above-mentioned antistatic agent combination.

[0074] From Example 1, Comparative Example 5, it can be seen that the use of heat resistant compatibilizer in HIPS system can better improve the surface resistance of HIPS composite material and still has a lower surface resistance after boiling in water for 7 days.

[0075] From Example 1, Comparative Example 6 and Comparative Example 7, it can be seen that the polyphenyl ether resin with melt flow rate in a certain range or the GPPS resin with number average molecular weight in a certain range can better improve the surface resistance of HIPS composite material and still has a lower surface resistance after boiling in water for 7 days.

[0076] The foregoing examples are illustrative only and are not meant to limit the scope of the methods described herein. The appended claims are intended to claim as broad a range as is allowed under the law. The examples presented herein are presented to demonstrate the application of the inventors. Therefore, the intention of the applicants is not to be limited by the selection of examples that illustrate the features of the application. Some numerical ranges recited in the claims are inclusive of the endpoints and are also inclusive of sub-ranges within the ranges. Where a range of values is recited, changes to the recited range of values can be made, and these changes are also intended to be encompassed by the appended claims.

Claims

1. A HIPS composite material, characterized in that, The HIPS composite material comprises the following components by weight: HIPS resin 49-70 parts, composite antistatic agent 18-25 parts, heat-resistant compatibilizer 10-20 parts, compatibilizer 2-6 parts, and toughening agent 3-5 parts. The composite antistatic agent comprises a first antistatic agent and a second antistatic agent; the first antistatic agent is sodium alkyl sulfonate containing 8-14 carbon atoms, and the second antistatic agent is alkyl oxypropyl dihydroxyethyl amine. The heat-resistant compatibilizer is selected from polyphenylene ether resin and / or GPPS resin. The melt flow rate of the polyphenylene ether resin under the test conditions of a temperature of 315°C and a load of 10 kg is 25 to 45 g / 10 min; the number average molecular weight of the GPPS resin is 4.0 x 10 4 ~ 8.5 x 10 4 g / mol.

2. The HIPS composite material according to claim 1, wherein, The mass ratio of the first antistatic agent to the second antistatic agent is 1:1-4.

3. The HIPS composite material of claim 1, wherein, The toughening agent is selected from one or more of styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene block copolymer, styrene-acrylonitrile-acrylate rubber, styrene-maleic anhydride copolymer, and methyl methacrylate-butadiene-styrene terpolymer.

4. The HIPS composite material of claim 3, wherein, The content of styrene in the toughening agent is ≤60wt%.

5. The HIPS composite of claim 1, wherein, The HIPS resin has a melt flow rate of 5-13 g / 10 min at 200℃ under a load of 5 kg.

6. The HIPS composite of claim 1, wherein, The compatibilizer is selected from one or more of polyethylene, polypropylene, chlorinated polyethylene, low-density polyethylene, and linear low-density polyethylene.

7. The HIPS composite of claim 6, wherein, The compatibilizer is linear low-density polyethylene.

8. The HIPS composite of claim 1, wherein, The first antistatic agent is sodium alkyl sulfonate containing 12-14 carbon atoms.

9. Process for the production of the HIPS composite material according to any one of claims 1 to 8, characterized in that, The HIPS resin, the composite antistatic agent, the heat-resistant compatibilizer, the compatibilizer, and the toughening agent are mixed, melt-extruded, and granulated to obtain the HIPS composite material.

10. Use of the HIPS composite material of any one of claims 1-8 in the field of electronics and electrical appliances.

Citation Information

Patent Citations

  • Antistatic PETG resin and manufacturing method thereof

    CN114193739A

  • Antistatic polyethylene wax and preparation method thereof

    CN118852767A